Decrease Level Of Candida Albicans in Children with The Practice of â€œPure Honeyâ€ Oral Hygiene - Alfiyanti, Dera; Hidayanti, Titi Nur (Universitas Muhammadiyah Semarang, 2018)
Background: Oral hygiene is an act of cleansing the entire area of the mouth, including teeth and gums to avoid infection. Purpose of hygiene to reduce dental plaque, reduce risk of oral cavity, eliminate tooth decay, gum, improve comfort in child.. Objective: This study aims to determine the effect of oral hygiene using 30% pure honey to the number of candida albicans in hospitalized children. Method: This study was a quasy experiment pre and post test with control group design. The data were analyzed with paired t-test dan independent paired samples t-test. The population of this study was all hospitalized children. The sample size is determined by purposive sampling technique, with a sample size of 20 (10 children were intervention group, 10 children were control group). Result: Mean number of candida pre testÂ of 38.90 CFU / ml and post test A total of 27.40 CFU / ml. The result of statistical test of separate parametric test in pairs of t-test p value of 0.001 (Î± = 0,05), so it can be concluded that there is oral hygiene effect using 30% pure honey to number of candida albicans child's mouth. Discussion: Hospitalized children were high risk population of nosocomial infection. There were many source of secondary infection such as infection by candida albicans. The recommendation of this research is that all children treated in hospital are done orally hygiene by using 30% pure honey